Using narrative evidence synthesis in HRM research: An overview of the method, its application, and the lessons learned. Issue 2 (24th October 2017) - Madden, Adrian; Bailey, Catherine; Alfes, Kerstin; Fletcher, Luke
Abstract : The use of systematic approaches to evidence review and synthesis has recently become more common in the field of organizational research, yet their value remains unclear and largely untested. First used in medical research, evidence review is a technique for identifying, evaluating, and synthesizing existing empirical evidence. With greater demand for the best evidence about "what works" in organizational settings, nuanced approaches to evidence synthesis have evolved to address more complex research questions. Narrative synthesis is perceived to be particularly suited to evaluating diverse evidence types spanning multiple disciplinary fields, characteristic of the HRM domain. This article evaluates the narrative evidence synthesis approach, explains how it differs from other techniques, and describes a worked example in relation to employee engagement. We consider its strengths, the challenges of using it, and its value in HRM research.